REPRODUCTIVE APPEARANCE OF BALI CATTLE AT SIMANTRI IN BADUNG REGENCY - Wimbavitrati, Kusumaning Arumsari; Sampurna, I Putu; Suatha, I Ketut (Buletin Veteriner Udayana, 2020)
This study aims to determine the component of reproduction appearance that has the highest diversity and correlation between bali cattle reproduction performance components at the Simantri in Gapoktan Badung regency. Sampling was done by full sampling technique at 50 Simantri using questionnaires and interviews to farmers and directly in the field. The data obtained were analyzed using factor simulation and presented with Biplot simulation, to illustrate the diversity and correlation of reproductive performance components. The results showed that the component of appearance that has the smallest diversity is the long pregnant, while the variable that has the greatest diversity is estrus postpartum. There is an experience between the age of puberty, the first mating, long pregnant, the first parturition, and between estrus postpartum and mating postpartum.